2020
DOI: 10.1016/j.biopha.2020.110668
|View full text |Cite
|
Sign up to set email alerts
|

Insights into antiviral mechanisms of remdesivir, lopinavir/ritonavir and chloroquine/hydroxychloroquine affecting the new SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 101 publications
2
101
0
Order By: Relevance
“…Consequently, an LPV/r combination may be useful in treating mild, moderate, and severe COVID-19 infection. 119 In a triple therapy study, LPV/r was potentially promising by suppressing the viral load, while methylprednisolone reduced the incidence of pneumonia and the need for ICU admission. 120 Ye et al (2020), in an early study in China involving 47 patients, revealed that lopinavir/ritonavir lowered body temperature and restored normal physiological functions more effectively than seen in a control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, an LPV/r combination may be useful in treating mild, moderate, and severe COVID-19 infection. 119 In a triple therapy study, LPV/r was potentially promising by suppressing the viral load, while methylprednisolone reduced the incidence of pneumonia and the need for ICU admission. 120 Ye et al (2020), in an early study in China involving 47 patients, revealed that lopinavir/ritonavir lowered body temperature and restored normal physiological functions more effectively than seen in a control group.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, remdesivir may have a place in patient treatment with mild to moderate COVID-19 disease. 119 , 134 Conversely, the initial studies with remdesivir failed to demonstrate clinical benefit over placebo; however, there were concerns that the investigations were underpowered. 32 , 135 Spinner et al (2020), in a study involving 596 COVID-19 patients, found those patients randomized to a 10-day course of remdesivir did not show a statistically significant improvement in their health status versus standard care randomized.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 virus replication requires the cleavage of viral polyproteins, and the proteases 3CLpro and PLpro are responsible for this cleavage. In vitro, lopinavir and ritonavir were found to inhibit 3CLpro, and thus reduce SARS-CoV-2 replication [ 19 ]. However, these drugs are poorly selective and high concentrations are required to achieve in vivo inhibition [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These protease inhibitors mimic the normal peptide linkage and bind to the substrate-binding pockets of viral enzymes such as papain-like cysteine proteinase (PLpro) and 3C-like proteinase (3CLpro). By inhibiting the enzyme activity, drugs prevent the proteolysis of Gag polyprotein precursors, which causes the formation of immature, non-infectious viral particles ( Uzunova et al, 2020 ).…”
Section: Antiviral Drugsmentioning
confidence: 99%